P23 Influence of a multi-strain probiotic on gut microbiome modulation and metabolic function, epithelial tight junction integrity and intestinal inflammation utilising a multi-compartmental in-vitro gut model of decompensated cirrhosis. (20th September 2022) - Moens, Frédéric; Abbeele, Pieter Van den; Maxan, Maria-Emanuela; Arefaine, Bethlehem; Said, Jawal; Basit, Abdul W; Gaisford, Simon; Patel, Vishal C
Abstract : Background/Aims: Decompensated cirrhosis (DC) is characterised by altered gut microbiome composition and function, intestinal barrier failure and immune dysfunction and inflammation, all hypothesised to contribute to increased risks of infection and hepatic decompensation. A live, multi-strain, aqueous probiotic suspension (Symprove™) that has undergone rigorous efficacy testing in other intestinal diseases including ulcerative colitis (Bjarnason et al, 2019) 1 and diverticular disease (Kvasnovsky et al, 2017) 2 is hypothesised to be of benefit in DC patients as a gut immunomodulating approach. The aims were to assess the effects of Symprove™ and metabolites derived from colonic fermentation on (i) microbiome composition, (ii) intestinal barrier integrity, (iii) immune markers, and (iv) wound healing. Such experimental measurements in-vivo are challenging in DC. We therefore employed an in-vitro dynamic, multi-compartmental gastrointestinal model (simulator of the human intestinal microbial ecosystem, equipped with a mucosal compartment, M-SHIME®) which was populated with faeces from DC patients. Methods: Faecal samples from three alcohol-related (all abstinent) DC patients were utilised in a M-SHIME® platform. Faeces were treated with Symprove™ with untreated samples used as controls. The impact of Symprove™ on mucosal and luminal bacterial diversity was evaluated by 16S rRNA gene sequencing and compared with previously assessed healthy control faeces. The effect on epithelial tight-junction integrity was measured utilising transepithelial electrical resistance (TEER) measurement of Caco-2/THP1-Blue™ co-cultures, metabolites (short chain fatty acids (SCFAs) and lactate), anti-inflammatory markers (IL-6, IL-10) and chemokines (IL-8, MCP-1). Scratch wound healing was evaluated using an in-vitro T84 cell culture model. Results: Treatment with Symprove™ resulting in an enrichment in Bifidobacteriaceae, Lactobacillaceae and Veillonellaceae levels in DC faeces. Estimated tight-junction integrity improved in all treated samples with TEER increasing. Anti-inflammatory cytokine production (NK-kB, IL6 and IL10) increased, whilst inflammatory chemokines (MCP-1 and IL-8) decreased. Symprove™ resulted in faster epithelial wound healing ( figure 1 ), with increased SCFA concentrations, in particular acetate and propionate, and lactate consumption, indicative of being a substrate for SCFA production. Summary/Discussion: Treatment with Symprove™ by exposure to DC faeces in an advanced in-vitro intestinal model exerts improvements in faecal microbiome composition, SCFA production, intestinal inflammation and epithelial wound healing. This is in keeping with protective effects ameliorating inflammation-induced intestinal barrier disruption, enhanced immunomodulatory effects and gut epithelial barrier restitution in cirrhosis. These mechanistic in vitro data provide the rationale a gut-modulating approach in cirrhosis and forms the basis for evaluation of this probiotic in the context of a placebo-controlled clinical trial in DC patients. References: Bjarnason I, Sission G, Hayee B. A randomised, double-blind, placebo-controlled trial of a multi-strain probiotic in patients with asymptomatic ulcerative colitis and Crohn's disease. Inflammopharmacology . 2019 Jun;27 (3):465–473. doi: 10.1007/s10787-019-00595-4. Epub 2019 May 3. PMID: 31054010; PMCID: PMC6554453. Kvasnovsky CL, Bjarnason I, Donaldson AN, Sherwood RA, Papagrigoriadis S. A randomized double-blind placebo-controlled trial of a multi-strain probiotic in treatment of symptomatic uncomplicated diverticular disease. Inflammopharmacology . 2017 May 20. doi: 10.1007/s10787-017-0363-y. Epub ahead of print. PMID: 28528364.